Body composition and somatotype of male Zimbabwean league basketball players - Makaza, D.; Amusa, L. O.; Goon, D. T.; Gundani, M. P.; Mugandani, S. C.; Toriola, A. L. (African Journal for Physical, Health Education, Recreation and Dance, 2011)
This study presents a profile of the body composition and somatotype characteristics of male Zimbabwean league basketball players, which information is lacking. Twenty six players aged 22.0±5.3 years were purposively sampled from the top teams of the Bulawayo Basketball Association. Anthropometric variables were measured using standardized procedures of the International Society for the Advancement of Kinanthropometry. Measurements included body mass, stretch stature, skinfolds (triceps, subscapular, biceps, iliac crest, supraspinale, abdominal, front thigh and medial calf), girths (arm relaxed, arm flexed and tensed, waist, gluteal and calf) and bone breadths (humerus and femur). Body mass index (BMI), waist-to-hip ratio (WHR), percentage body fat (%BF), fat mass (FM), fat-free mass (FFM), fat mass index (FMI) and fatfree mass index (FFMI) were calculated as body composition variables. Heath-Carter somatotype method was used in determining the somatotype of the participants. The results indicated mean body mass of 68.39 ± 9.73 kg, height 1.79 ± 0.07m, sum of six skinfolds 50.4 ± 37.2 mm, %BF 8.92 ± 5.88, BMI 21.21 ± 2.36, WHR 0.80 ± 0.02, FM 6.61 ± 6.05 kg, FFM 61.78 ± 6.95 kg, FMI 2.01 ± 1.69, and FFMI 19.13 ± 1.65 among the participants. None of these values indicate a threat or proneness to hypokinetic health problems. There are no significant differences among the players at different playing positions in terms of all the variables, except height. The mean somatotype for the players was 1.7-3.9-3.7 (ectomorph-mesomorph). The major somatotype categories were 38% mesomorphic-endomorphs and 31% mesormorphic-ectomorphs. There are no significant differences in somatotype among players at different positions. The players were found to be shorter and lighter when compared with players elsewhere